(untitled) (Pedagogy of Higher and Secondary Education, 2008)
The author studies psychological and pedagogical theories which have comprised the methodological basis of distance education abroad Short history of the distance learning is presented. Besides, main psychological approaches of learning which have contributed to the distance education are under the view.